UTILIZATION OF CINNAMON BARK (CINNAMOMUM BURMANNI) EXTRACT AS A NATURAL INHIBITOR FOR THE CONTROL OF CORROSION RATE IN IRON METAL - Sembiring, Aggryppyne Keyne Oberta; Putra, Anak Agung Bawa; Ratnayani, Oka (Jurnal Ilmu Pendidikan Indonesia, 2023)
Iron is a metal that is very susceptible to corrosion. Corrosion of iron can occur due to reaction with the surrounding environment, causing damage to ferrous metal. The use of organic inhibitors such as cinnamon bark is considered to be able to suppress the corrosion rate, because in the inhibitor there are tannin compounds that are able to form complex compounds with Fe(III) on the metal surface. Bark consists of an tannins, makes this cinnamon bark capable of being an organic inhibitor. The purpose of this riset was to determine the effect of inhibitor concentration and variation of corrosive media on the corrosion rate, and to determine whether cinnamon bark extract had the potential to be used as an inhibitor. The method used is weight loss in which iron is immersed in various corrosive media for 48 hours without the addition of inhibitors and with the addition of inhibitors of 10; 20; 30; 40; 50; 60; 70; 80; 90; and 100 ppm. The highest corrosion rate without the addition of inhibitors occurred in iron immersed in salt media (NaCl 3.5%) of 53.5371 mpy, and the lowest corrosion rate occurred in iron immersed in neutral media (aquadest) of 15.6342 mpy. The corrosion rate also decreases with the increase in the concentration of the added inhibitor. In other words, this cinnamon bark extract has the potential to be used as an organic inhibitor.